2022
DOI: 10.1177/08853282221123452
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable biodegradability of low-swelling hydrogels prepared from recombinant peptides based on human collagen type 1

Abstract: An ideal hydrogel for tissue engineering and regenerative therapy is cytocompatible, biocompatible, and has low-swelling characteristics. Recently, a novel low-swelling hydrogel with a homogenous structure was developed by crosslinking a recombinant peptide, modeled on human collagen type 1 (RCPhC1), with a four-arm polyethylene glycol (tetra-PEG). Here, we hypothesized that the biodegradability of the RCPhC1 hydrogel was adjustable by altering its initial polymer concentration. Three types of RCPhC1 hydrogels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The collagen fibers in cephalopods contain interstitial tissue and a large distance between tissue cells, this characteristic appears in artificially cultured tissue and animals breathing through the skin or soft tissue. For instance, Octopus vulgaris traps the air taken by the animal through the skin to the skin tissue and then uses it for breathing process matching the higher terristerials animals (Grześkowiak, 2022;Nakano et al, 2022;Patte et al, 2022;Wang et al, 2022;Yin et al, 2022;Abd Elrheem, 2023). The interstitial area functions as similar as the lower lung, with lower content of dissolved oxygen which is adequate for survival, and this is common in kingdom Animalia such as hagfish (Smith et al, 2010;Birk et al, 2018;Eom et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collagen fibers in cephalopods contain interstitial tissue and a large distance between tissue cells, this characteristic appears in artificially cultured tissue and animals breathing through the skin or soft tissue. For instance, Octopus vulgaris traps the air taken by the animal through the skin to the skin tissue and then uses it for breathing process matching the higher terristerials animals (Grześkowiak, 2022;Nakano et al, 2022;Patte et al, 2022;Wang et al, 2022;Yin et al, 2022;Abd Elrheem, 2023). The interstitial area functions as similar as the lower lung, with lower content of dissolved oxygen which is adequate for survival, and this is common in kingdom Animalia such as hagfish (Smith et al, 2010;Birk et al, 2018;Eom et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The Siphonopoda indicates the presence of a siphon, so the old term is true nomenclature and right in classification. The cartilage formation process in all animals' appearance of cells is responsible for the formation of bone (Depew, 2008;Debiais-Thibaud, 2019;Molnar et al, 2022). Some authors identified the presence of a permanent layer of conchiolin as collagen fibers' origin; however, they considered the appearance of protostome characters to be the remains of animal creatures (Gong et al, 2012;Ruiz, 2020;Whalen et al, 2022;Salas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%